New drugs registered in Brazil from 2003 to 2013: analysis from the perspective of child health (Brazilian Journal of Pharmaceutical Sciences, 2022)
This study aims to analyze the new drugs registered in Brazil from 2003 to 2013 from the perspective of childcare needs, drug safety and considering the disease burden of the country. This is a retrospective cohort study including new drugs registered in Brazil between 2003 and 2013. Drug indications were related to the Disability-Adjusted Life Year (DALY) of the 2015 Global Burden of Disease Study. Association between the number of new drugs and DALY was determined by Spearman’s coefficient. Post-marketing safety alerts specific to the pediatric population have been identified in the WHODrug Information Bulletin and on websites of drug regulatory agencies. A total of 134 new drugs were included in the cohort and 46 (34.3%) had a pediatric indication. There was no evidence of an association between the disease burden in children in Brazil and the number of pediatric drugs. The safety alert data associated with the pediatric population published after registration of the new drugs were scarce. The number of new drugs launched in Brazil with a pediatric indication was small, reflecting the international challenges of developing effective and safe medicines for children. No association was found between the number of new drugs and the disease burden.